Microstructural characterization of C/C-SIC composites after oxidation with oxyacetylene gas in open atmosphere - Srivastava V.K.; Singh S. (My University, 2025)
C/C-SiC composites plates were directly exposed with an oxyacetylene gas welding flame to understand the effect of temperature (>1000°C) in open atmosphere. Duration of exposure time was increased to measure the weight loss and performance of composites. SEM and TG analysis were performed to see the microstructural behavior of C/C-SiC composites after the exposure of oxyacetylene gas flame in open atmosphere. The results show that the weight loss increases with increase of exposure time clearly indicating that the excess amount of carbon is oxidized to form carbon mono-oxide. The matrix materials undergo pyrolysis reactions within short periods of time generating volatiles and leaving behind a porous skeleton of carbon fibres. Scanning Electron Microscopy (SEM) fractograph of fractured samples indicates that fibres debonded, broken and pull out due to increase of applied load, because, excess amount of matrix oxidized with the effect of high temperature.